DIGITALIZATION OF LOGISTICS PROCESSES, RESOURCE MANAGEMENT AND OPERATIONAL PLANNING IN THE STATE SPECIAL TRANSPORT SERVICE - Prodan, D. Ye.; Rybalchenko, L. V.; Chubenko, O. I.; Bibik, M. V. (Systems and Technologies, 2025)
The article deals with the topical problem of digitalization of logistics processes, resource management and operational planning in the conditions of specific tasks of the State Special Transport Service (hereinafter – the State Support Service). The introduction of digital technologies makes it possible to significantly increase the efficiency of managing material and technical resources, reduce decision-making time and optimize internal processes, which is especially important if the tasks of ensuring the continuous functioning of the critical transport infrastructure of the state. The study identifies a number of key initiatives aimed at introducing a single digital logistics and resource management system, geoinformation monitoring of infrastructure facilities, automation of operational planning and response, as well as the development of mobile applications for enhanced personnel coordination. It is noted that the use of geoinformation systems (GIS) makes it possible to visualize and quickly analyze the state of critical transport infrastructure, ensuring timely repair and repair work and increasing the overall safety of transport units.The research methodology involves a comparative analysis of modern digital platforms, mathematical modeling of logistics processes, as well as the use of statistical methods to evaluate the effectiveness of implementation of initiatives. To confirm hypotheses on the impact of digitalization on efficiency and planning accuracy was Experimental modeling was conducted on the basis of real data on the use of resources and vehicles in the units of the State Summer Service.The results demonstrate a reduction in time and resources, as well as increasing the response rate through timely processing of critically important information. On the basis of comparison with previous studies and areas of digital transformation in the military and transport spheres, it is concluded that the proposed measures can ensure a significant increase in the efficiency of the State Support Service. Prospective areas of further research are proposed, including integration with other state and military structures to enhance the interaction and expand the functional capabilities of digital platforms.